Renal protective effect of Melothria maderaspatana leaf fraction on uninephrectomized deoxycorticosterone acetate-salt hypertensive rats - Veeramani, Chinnadurai; Al-Numair, Khalid S.; Chandramohan, Govindasamy; Alsaif, Mohammed A.; Pugalendi, Kodukkur Viswanathan (Progress in Nutrition, 2014)
This study was designed to investigate the renal protective effect of ethyl acetate fraction of Melothria maderaspatana (EAFM) leaf on uninephrectomized deoxycorticosterone acetate (DOCA)-salt hypertensive rats. A midscapular incision was made on each rat and the left kidney was excised after ligation of the renal artery. The surgical wound was closed using an absorbable suture. After one week recovery period, hypertension was induced by subcutaneous injection of DOCA-salt solution, twice a week, and the rats received a 1% sodium chloride solution as drinking water throughout the experimental period. EAFM or nifedipine was administered orally once a day for 6 weeks. Administration of DOCA-salt significantly increased the mean arterial pressure and heart rate while treatment with EAFM significantly lowered the blood pressure. In DOCA-salt rats, the level of kidney function markers such as urea, uric acid and creatinine were increased significantly and treatment with EAFM brought these parameters to control rats. In addition, the levels of renin, angiotensin II and aldosterone were decreased significantly in hypertensive rats and administration of EAFM brought these parameters to normal levels. The present study indicated that the EAFM provides good blood pressure control and also protect the renal damage by preventing the abnormal activities of plasma renin, angiotensin II and aldosterone as evidenced by decreased plasma levels of urea, uric acid and creatinine.